2002
DOI: 10.1037/0022-3514.82.3.314
|View full text |Cite
|
Sign up to set email alerts
|

The inaction effect in the psychology of regret.

Abstract: Previous research showed that decisions to act (i.e., actions) produce more regret than decisions not to act (i.e., inactions). This previous research focused on decisions made in isolation and ignored that decisions are often made in response to earlier outcomes. The authors show in 4 experiments that these prior outcomes may promote action and hence make inaction more abnormal. They manipulated information about a prior outcome. As hypothesized, when prior outcomes were positive or absent, people attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(248 citation statements)
references
References 56 publications
8
226
0
7
Order By: Relevance
“…Similarly, Zeelenberg et al (2002) argue that action might be more normal than inaction when we consider previous outcomes; in particular, they claim that when a soccer team loses by a large margin, it becomes more normal for the coach to act in the next game (replace players in the opening team) than not to act (keep the same players), a claim that is supported by their experimental findings.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, Zeelenberg et al (2002) argue that action might be more normal than inaction when we consider previous outcomes; in particular, they claim that when a soccer team loses by a large margin, it becomes more normal for the coach to act in the next game (replace players in the opening team) than not to act (keep the same players), a claim that is supported by their experimental findings.…”
Section: Introductionsupporting
confidence: 53%
“…Of particular relevance in these cases are the results of Zeelenberg et al (2002) about the effect of previous outcomes on what is considered normal to do. They found that following a bad outcome (losing by a large margin in a previous soccer game), subjects consider action (changing the opening team) more normal than inaction, but following a good outcome (winning a previous game), inaction is considered more normal.…”
Section: Resultsmentioning
confidence: 99%
“…This temporal pattern (the inaction effect; Zeelenberg, van der Bos, van Dijk & Pieters, 2002) is a robust finding in studies involving autobiographical regrets. It has been demonstrated in the general population (Feeney et al, 2005;Feldman, Miyamoto & Loftus, 1999), among the intellectually gifted (Hattiangadi et al, 1995), and in several cultures (Bonnefon, & Zhang, 2008;Gilovich et al, 2003;Jokissari, 2003;Timmer et al, 2005).…”
Section: Agency and Autobiographical Regretsmentioning
confidence: 58%
“…It has also been shown to be sensitive to a number of manipulations and can depend on such things as whether an action is consistent with a person"s personal orientation (Seta, McElroy & Seta, 2001) ,whether information about prior (Zeelenberg, van der Bos, van Dijk, & Pieters, 2002) or alternative (Ritov & Baron, 1995) outcomes is available to the decision-maker, whether an outcome is seen as reversible (Abendroth & Diehl, 2006), and whether the decisions being judged are presented in a within-or between-subjects design (N"gbala & Branscombe, 1997;Zhang, Walsh & Bonnefon, 2005). The action effect continues to be explored in scenario studies (Byrne & McEleney, 2000;Feeney & Handley, 2006;Walsh & Byrne, 2007;Zeelenberg, van der Bos, van Dijk & Pieters, 2002). By locating regret within a decision-making framework and emphasising the role of counterfactuals, Kahneman and Tversky"s (1982) vignette studies shaped the way subsequent regret research was conducted, even when researchers adopted a different tack and moved away from laboratory studies and into the field to examine people"s actual autobiographical regrets.…”
Section: Agency and Counterfactual Thinkingmentioning
confidence: 99%
“…Thus, our results provide first suggestive evidence that coaches may be influenced by behavioural concerns when following the heuristic to not change winning teams. The psychological scenario study of Zeelenberg et al (2002) shows that behaving according to the "never change a winning team" heuristic decreases regret, irrespective of the team performance. Herding (Banjeree 1992;Bikhchandani et al 1992) and social pressure (Akerlof 1980;Bernheim 1994) may be other behavioural reasons why coaches follow the "never change a winning team" heuristic.…”
Section: Introductionmentioning
confidence: 99%